Systematic reviews showed insufficient evidence for clinical practice in 2004: What about in 2011? the next appeal for the evidence-based medicine age - Villas Bôas, Paulo José Fortes [UNESP]; Spagnuolo, Regina Stella [UNESP]; Kamegasawa, Amélia [UNESP]; Braz, Leandro Gobbo [UNESP]; Valle, Adriana Polachini do [UNESP]; Jorge, Eliane Chaves [UNESP]; Yoo, Hugo Hyung Bok [UNESP]; Cataneo, Antonio José Maria [UNESP]; Corrêa, Ione [UNESP]; Fukushima, Fernanda Bono [UNESP]; Do Nascimento, Paulo [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; et al. (Wiley, 2013)
Rationale and aim The aims of the Cochrane systematic reviews are to make readily available and up-to-date information for clinical practice, offering consistent evidence and straightforward recommendations. In 2004, we evaluated the conclusions from Cochrane systematic reviews of randomized controlled trials in terms of their recommendations for clinical practice and found that 47.83% of them had insufficient evidence for use in clinical practice. We proposed to reanalyze the reviews to evaluate whether this percentage had significantly decreased. Methods A cross-sectional study of systematic reviews published in the Cochrane Library (Issue 7, 2011) was conducted. We randomly selected reviews across all 52 Cochrane Collaborative Review Groups. Results We analyzed 1128 completed systematic reviews. Of these, 45.30% concluded that the interventions studied were likely to be beneficial, of which only 2.04% recommended no further research. In total, 45.04% of the reviews reported that the evidence did not support either benefit or harm, of which 0.8% did not recommend further studies and 44.24% recommended additional studies; the latter has decreased from our previous study with a difference of 3.59%. Conclusion Only a small number of the Cochrane collaboration's systematic reviews support clinical interventions with no need for additional research. A larger number of high-quality randomized clinical trials are necessary to change the 'insufficient evidence' scenario for clinical practice illustrated by the Cochrane database. It is recommended that we should produce higher-quality primary studies in active collaboration and consultation with global scholars and societies so that this can represent a major component of methodological advance in this context. © 2012 John Wiley & Sons Ltd.
Keywords: clinical medicine; clinical trials; Cochrane reviews; evidence-based medicine; limitations; meta-analysis; research; review literature; clinical practice; Cochrane Library; cross-sectional study; evidence based medicine; human; meta analysis; priority journal; review; systematic review